1997
DOI: 10.1080/00926239708404413
|View full text |Cite
|
Sign up to set email alerts
|

Premature Ejaculation: A psychophysiological review

Abstract: This review examines the most common male sexual dysfunction, premature ejaculation (PE). The prevalence, classification, neurophysiology, neuropharmacology, and psychological studies that offer evidence useful for understanding and clinically evaluating PE are reviewed. It is proposed that there are two basic kinds of PE: biogenic and psychogenic. Studies reporting pharmacological aspects of ejaculation offer some suggestions regarding the mechanisms of ejaculation as well as possible pharmacologic aid for so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 85 publications
1
67
0
5
Order By: Relevance
“…Of these three, PE is likely the most prevalent sexual dysfunction according to the results of numerous epidemiological studies. 1,2,13,22,27 Overall, the prevalence rate of PE falls somewhere between 25 and 40% in the global population of men across all age groups. 20,24,[27][28][29] However, past data on the overall prevalence of PE are varied, once again, in great part owing to the lack of prior standardization of the definition of PE and of criteria for patient enrollment in epidemiologic studies.…”
Section: Interpretation and Standards For Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these three, PE is likely the most prevalent sexual dysfunction according to the results of numerous epidemiological studies. 1,2,13,22,27 Overall, the prevalence rate of PE falls somewhere between 25 and 40% in the global population of men across all age groups. 20,24,[27][28][29] However, past data on the overall prevalence of PE are varied, once again, in great part owing to the lack of prior standardization of the definition of PE and of criteria for patient enrollment in epidemiologic studies.…”
Section: Interpretation and Standards For Clinical Trialsmentioning
confidence: 99%
“…13,14 This classification system arises from the realization that psychologically or behaviorally based sex therapies have poor long-term success rates over time. 15,16 Thus, perhaps a biogenic cause of PE exists that is refractory to psychological sex therapy.…”
Section: Defining and Categorizing Pementioning
confidence: 99%
“…8,9 While a few of the studies have evaluated the effectiveness of ED treatments in men with comorbid PE and ED, 10,11 very few have examined the prevalence of these comorbid conditions. A large survey that included 12 134 men from the United States, Germany, and Italy recently found that 7.2% of men met the criteria for both PE and ED.…”
Section: Introductionmentioning
confidence: 99%
“…9 As such, these PDE-5 inhibitors are likely to be a common concomitant medication, and the potential for drug-drug interactions with dapoxetine must be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…3 Among the sexual side effects (in patients without PE) most commonly associated with selective serotonin reuptake inhibitor drugs (SSRIs) are delayed ejaculation and absent or delayed orgasm. These effects are present also in subjects with PE, so that SSRIs seem to be a successful treatment of PE.…”
mentioning
confidence: 99%